Comparative Analysis Quality of Innovative Pasta from Quinoa - Gęsiński, Krzysztof; Ruszkowska, Millena (Scientific Journal of Gdynia Maritime University, 2022)
The aim of this study was to evaluate the quality of innovative quinoa pasta by assessing its culinary qualities. The products were compared with traditional wheat pasta. Four innovative products containing Chenopodium quinoa, available on the Polish market, were selected for the study. The culinary properties were determined by evaluating the weight gain factor, loss of dry matter during cooking, and an organoleptic evaluation and colour of pasta before and after cooking. The study showed that the culinary quality of the innovative products varied and depended on the raw material composition. A correlation was found between pasta properties and the proportion of quinoa and wheat flour in the products and the nutrient content. Pasta with a higher proportion of quinoa was characterized by good cooking properties.